What's the point? The importance of meaningful work - Fletcher, Luke; Robinson, Dylis (Brighton, 2016)
"We spend a lot of our time at work. Around eight hours a day, for at least 40 weeks every year, for 40 years or so. Dilys Robinson and Luke Fletcher make a well-supported case for the currently popular but long-standing concept of meaningfulness, concluding that: 'the positive benefits of offering meaningful work – higher engagement, reduced absence and better performance – suggest that it is worthwhile to make the effort."